Gentamicin coated iron oxide nanoparticles as novel antibacterial agents. (6th September 2017) - Bhattacharya, Proma; Neogi, Sudarsan
Abstract: Applications of different types of magnetic nanoparticles for biomedical purposes started a long time back. The concept of surface functionalization of the iron oxide nanoparticles with antibiotics is a novel technique which paves the path for further application of these nanoparticles by virtue of their property of superparamagnetism. In this paper, we have synthesized novel iron oxide nanoparticles surface functionalized with Gentamicin. The average size of the particles, concluded from the HR-TEM images, came to be around 14 nm and 10 nm for unmodified and modified nanoparticles, respectively. The magnetization curve M ( H ) obtained for these nanoparticles are typical of superparamagnetic nature and having almost zero values of coercivity and remanance. The release properties of the drug coated nanoparticles were studied; obtaining an S shaped profile, indicating the initial burst effect followed by gradual sustained release. In vitro investigations against various gram positive and gram negative strains viz Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Bacillus subtilis indicated significant antibacterial efficiency of the drug-nanoparticle conjugate. The MIC values indicated that a small amount like 0.2 mg ml −1 of drug capped particles induce about 98% bacterial death. The novelty of the work lies in the drug capping of the nanoparticles, which retains the superparamagnetic nature of the iron oxide nanoparticles and the medical properties of the drug simultaneously, which is found to extremely blood compatible.